OBSERVATIONS ON THE PLANKTON ECOLOGY OF PULICAT LAKE - Kaliyamurthy, M (Indian Journal of Fisheries, 2011)
Observations made on the spatial, temporal and tidal variations of theplankton of Pulicat Lake during April 1968 to March 1970 indicated that theplankton was rich in quantity and quality at stations nearer to the mouththan at the upper reaches. The primary peak of the phytoplankton occurredduring May-July and that of the zooplankton in April-May. A close similarity wasnoticed in the characteristics of plankton between the lake and the coastal watersof Madras. A marked seasonal cycle in the phytoplankton production related tottdal leases was observed, especially during summer and postmonsoon seasons.The zooplankton populations varied more with the time of the day than with thetide. Phytoplankton showed some direct relationship, while zooplankton and settlingvolume of plankton had no such relationship with the salinity conditions. Thezooplankton appeared to have direct correlation with water temperature, but thelatter had no apparent effect on i^ytoplankton. Zoi^lankton production of thesouthern sector of the lake was 1.4 to 2 times higher than that of the northernsector, which, was reflected in the fish yield of the respective zones.